Pengaruh amalan-amalan sumber manusia terhadap pengekalan Pegawai Meteorologi di sektor awam - Aminah, Ismail (2014)
The objective if this research paper is to study the effects of human resource practices on retention of Meteorological Officers in the public sector. The human resource practices that have been chosen are work environment and job design, hiring and promotions, employee recognition, rewards and compensation, and employee performance appraisal and career development. This involves 95 of 144 respondents that were selected using random sampling. The respondents filled out a questionnaire that was emailed to them to measure and test the organisational initiatives and practices for employee retention. Using SPSS 22.0 to test the hypothesis, correlation and regression analyses was conducted. The findings show that two human resource practices, which are work environment and job design, and hiring and promotions, have an effect on employee retention. The other two human resource practices, which are employee recognition, rewards and compensation, and employee performance appraisal and career development, do not affect employee retention. These findings reflect the practices in the Meteorological Officers' organisation that contribute to an understanding of the theoretical and practical implications of the role of human resource practices on retention of Meteorological Officer in the public sector.